2021
DOI: 10.1101/2021.11.18.467545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Slow fluctuations in ongoing brain activity decrease in amplitude with ageing yet their impact on task-related evoked responses is dissociable from behaviour

Abstract: In humans, ageing is characterized by decreased brain signal variability and increased behavioural variability. To understand how reduced brain variability segregates with increased behavioural variability, we investigated the association between reaction time variability, evoked brain responses and ongoing brain signal dynamics, in young (N = 36) and older adults (N = 39). We studied the electroencephalogram (EEG) and pupil size fluctuations to characterize the cortical and arousal responses elicited by a cue… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…Research has recently revealed that the neural variabilities in the brain, previously considered meaningless noise or measurement error [8,9], reflect these behavioral variabilities. Neural variability is believed to contain valuable information about brain dynamics, which is not only related to low-and high-level cognition in health and clinical participants [8] but also underlies the plasticity and adaptability of human behavior [9,10] . Brain neural variability can take many forms.…”
Section: Introductionmentioning
confidence: 99%
“…Research has recently revealed that the neural variabilities in the brain, previously considered meaningless noise or measurement error [8,9], reflect these behavioral variabilities. Neural variability is believed to contain valuable information about brain dynamics, which is not only related to low-and high-level cognition in health and clinical participants [8] but also underlies the plasticity and adaptability of human behavior [9,10] . Brain neural variability can take many forms.…”
Section: Introductionmentioning
confidence: 99%